Cloud Computing, Big Data and the Industry 4.0 Reference Architectures - Velásquez, Nancy (2018)
The Industry 4.0 promotes the use of Information and Communication Technologies (ICT) in manufacturing processes to obtain customized products satisfying demanding needs of new consumers. The Industry 4.0 approach transforms the traditional pyramid model of automation to a network model of interconnected services, combining operational technology (OT) with Information Technology (IT). This new model allows the creation of ecosystems enabling more flexible production processes through connecting systems and sharing data. In this context, cloud computing and big data are critical technologies for leveraging the approach. Thus, this paper analyzes cloud computing and big data under the lenses of two leading reference architectures for implementing Industry 4.0: 1) the Industrial Internet Reference Architecture (IIRA), and 2) the Reference Architecture Model Industrie 4.0 (RAMI 4.0). A main contribution of this paper is to present a comparative analysis of IIRA and RAMI 4.0, discussing needs, benefits, and challenges of applying cloud computing and big data in the Industry 4.0.